Impacts of climate change on corn production in Mexico - Cruz-González, Alejandro; Arteaga-Ramírez, Ramón; Sánchez-Cohen, Ignacio; Soria-Ruiz, Jesús; Monterroso-Rivas, Alejandro Ismael (Revista Mexicana de Ciencias Agrícolas, 2024)
Anthropogenic activities have added enough to cause important alterations in the climate at a global level; in the last 20 years, a phenomenon of extreme characteristics called ‘climate change’ has worsened, which has been responsible for causing climate variability, the level of affectation of which extends to all geographical scales. This research was carried out in 2022 with the aim of knowing the impacts of climate change on the productive system of the corn crop in Mexico, given its great nutritional, cultural, and economic relevance. It describes the climate variability and extreme events that occur in Mexico and that in some way have a direct relationship with corn production, such as precipitation, temperature, frosts, hailstorms, droughts, and floods. Worldwide, Mexico stands out in the first places in production and consumption of corn; the current population exceeds 126 million people, and it is a condition that manifests a great demand, having to make a strong export of the grain year after year, showing the unsustainability of the country’s food security. This situation is aggravated when climate change and climate variability directly affect the most important requirements for the establishment of a crop, and that directly affect all stages of growth and development, presenting a decrease in current and future yield.